Colonization of Different Grapevine Tissues by Plasmopara viticola—A Histological Study - Fröbel, Sarah; Zyprian, Eva (Frontiers in Plant Science, 2019)
Plasmopara viticola, the downy mildew pathogen, is one of the most important pathogens in 4 European viticulture. This oomycete infects grapevine leaves via zoospores that encyst at stomata. 5 A primary germ tube enters the substomatal cavity and develops a tubular network of hyphae 6 that proliferate intercellularly and parasitize the leaf mesophyll cells by haustoria. Leaf infections 7 have thus been the primary object of multiple studies concerning the physiology of the pathogen 8 and defense reactions of grapevines. Besides leaves, this oomycete pathogen is able to spread 9 throughout the plant tissue. As shown here by microscopy, it colonizes leaf petioles, shoots, 10 berries and seeds. Evidence is provided showing that this process is facilitated by formation of 11 special fan-shaped hyphae that seem to be necessary to overcome physical barriers in plant 12 tissues. Physical obstacles are mainly constituted by vascular tissue in leaf veins, leaf petioles 13 and shoots. In grapevine shoots, the mycelium seems to extend along the cambial layer between 14 xylem and phloem tissue. Infected young berries are completely colonized on the inside. Older 15 infected “leather berries” show glossy appositions of the fan-shaped hyphae at the inner side of 16 the berry skin. The seeds from that stage of infestation are devoid of endosperm and embryo and 17 biologically dysfunctional. Furthermore, a classification system for P. viticola infection based on 18 the degree of infections in petioles and shoot tips is presented. This study contributes to a better 19 understanding of downy mildew pathogenesis in grapevine.